Seismic behaviour of Beris Dam under six earthquake excitations by using finite element method / Rozaina Ismail ... [et al.] - Ismail, Rozaina; Moktar, Nurul Nabilah; Sukati, Nurul Damia; Abd Halim, Ainnur Zulsyamilatil Huda; Fitri Erwan, Dayang Nur Erliyani; Ibrahim, Azmi; Mohd Amin, Norliyati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This paper focused on the behavior of the dam when exposed to seismic loading and ability of the dam to withstand the applied loads from various seismic events. The chosen concrete dam to be referred to in the twodimensional analysis is Beris Dam located in Kedah, Malaysia. A nonlinear dynamic analysis is chosen to analyse the behavior of Beris Dam under selected ground motion. Analysis of the dam is performed using the finite element method by utilizing ABAQUS software. From the cracking analysis pattern, a crack appeared at the upstream face of the dam caused mainly by the excessive tensile stress. Based on the results, the displacement of the dam is increased with the increasing of ground motion data where the displacement occurred in the horizontal direction. The maximum stresses exerted by the dam structure do not exceed the allowable capacity of concrete dams. The stress behaviour of the dam was satisfactorily acceptable as the maximum normal stress and shear stress of the dam when numerous seismic loadings are applied do not exceed the allowable stress capacity which is 800 kN/m2.